A Comparative Study on the Understanding of Food Labels Among Young Adults (18–25 Years) in Varanasi and Delhi - Anamika Gautam; Vatta, Lalita (Indian Journal of Extension Education, 2026)
With the rise in processed food consumption and the spread of non-communicable diseases, the importance of food labels has grown to help prevent these issues and inform consumers about their dietary choices and their effects. A food label on pre-packed food products is very significant. It provides information on what we should eat or purchase. Label literacy means a person’s ability to understand, comprehend, and utilise this information while purchasing pre-packed food items. In the modern world, people are so occupied with their lives that they often lack the time to eat, leading to a growing demand for packaged food products. This research was conducted to assess the level of understanding of food labels among individuals aged 18-25 in Delhi and Varanasi during August 2025. The study employed a survey method, gathering data through random sampling techniques. Data analysis was conducted using Excel and SPSS version 16. Findings reveal that most participants from both locations read nutritional labels easily, indicating awareness. A significant number of respondents say that the lack of time was the main challenge, while most approved nutritional labels are warning labels on food packets.